2016
DOI: 10.4172/2376-0281.1000192
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Fetal Alcohol Spectrum Disorder: Meeting Needs Across the Lifespan

Abstract: Background: Fetal Alcohol Spectrum Disorder (FASD) is a complicated disability resulting in a diverse, highneeds population for whom intervention is critical to optimize functional competence and reduce the emergence of adverse outcomes. Researchers have been evaluating intervention efforts for FASD to inform practice and policy decision-making. Objective: The current review provides a synopsis of the current state of evidence for intervention research in FASD, with consideration of how our growing understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Although it is recognized that responses for individuals with FASD should be coordinated, long-term, and informed by the neurocognitive vulnerabilities associated with PAE (Mela et al, 2019), there is currently a lack of consolidated information about responses intended to support positive mental health and substance use outcomes in this population. Several review studies have been published in the last decade on FASD interventions more broadly (e.g., Paley & O'Connor, 2011;Peadon et al, 2009;Pei et al, 2016;Petrenko & Alto, 2017;Reid et al, 2015). However, none of these have been focused specifically on mental health or substance use outcomes for individuals with FASD, despite there being a notable gap in this area (Pei et al, 2016).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is recognized that responses for individuals with FASD should be coordinated, long-term, and informed by the neurocognitive vulnerabilities associated with PAE (Mela et al, 2019), there is currently a lack of consolidated information about responses intended to support positive mental health and substance use outcomes in this population. Several review studies have been published in the last decade on FASD interventions more broadly (e.g., Paley & O'Connor, 2011;Peadon et al, 2009;Pei et al, 2016;Petrenko & Alto, 2017;Reid et al, 2015). However, none of these have been focused specifically on mental health or substance use outcomes for individuals with FASD, despite there being a notable gap in this area (Pei et al, 2016).…”
Section: Current Studymentioning
confidence: 99%
“…Several review studies have been published in the last decade on FASD interventions more broadly (e.g., Paley & O'Connor, 2011;Peadon et al, 2009;Pei et al, 2016;Petrenko & Alto, 2017;Reid et al, 2015). However, none of these have been focused specifically on mental health or substance use outcomes for individuals with FASD, despite there being a notable gap in this area (Pei et al, 2016). To fill this gap, we conducted a systematic literature review to collate the findings of all existing research related to interventions that improve mental health and substance use outcomes for individuals with PAE/FASD across the life course.…”
Section: Current Studymentioning
confidence: 99%
“…The work established by the PSA is now spread across three networks in Calgary but the involvement of social work is still considered important. A Coaching Families programme run out of Toronto and Edmonton also uses similar advocacy and mentoring strategies and has been shown to be effective (Leenaars et al, 2012; Pei et al, 2016; Petrenko and Alto, 2017).…”
Section: Examples Of Effective Practice Modelsmentioning
confidence: 99%
“…However, research into the lived experience of parents and caregivers has revealed a perceived lack of knowledge and understanding of FASD by health and social service professionals, reflected through inadequate support and ineffective service provision (Breen and Burns, 2012; Salmon, 2008). There is a small but growing body of research into clinical interventions that attempt to improve the neurocognitive impairments associated with FASD (see Olson, 2016; Peadon et al, 2009; Pei et al, 2016; Petrenko and Alto, 2017). However, few studies document specific social work and social service interventions and approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent studies have found that self-regulation and executive function trainings result in improved parent-reports, inhibitory control, and storytelling (Nash et al, 2015; Wells, Chasnoff, Schmidt, Telford, & Schwartz, 2012). Computerized and attention focused interventions have also been moderately efficacious (Kerns, Macsween, Vander Wekken, & Gruppuso, 2010; Pei, Flannigan, Walls, & Rasmussen, 2016). Math intervention studies that were developed in concert with the neuropsychological profile associated with prenatal alcohol exposure (Math Interactive Learning Experience, MILE) have demonstrated significant gains in both pilot studies and community-based intervention (Kable et al, 2015; Kable et al, 2007).…”
Section: Integrated Evaluation and Diagnostic Interpretationmentioning
confidence: 99%